Moonbound eaudiobook A novel. - Sloan, Robin (Macmillan Audio, 2024)
Robin Sloan expands the Penumbraverse to new reaches of time and space in a rollicking far-future adventure. In Moonbound , Robin Sloan has written a novel with the full scope and ambitious imagination of the very books that lit the engines of Mr. Penumbra's 24-Hour Bookstore : an epic quest as only Sloan could conceive it, mixing science fiction, fantasy, good old-fashioned literary storytelling, and unrivaled enthusiasm for what's next. It is eleven thousand years from now . . . A lot has happened, and yet a lot is still very familiar. Ariel is a boy in a small town under a wizard's rule. Like many adventurers before him, Ariel is called to explore a world full of unimaginable glories and challenges: unknown enemies, a mission to save the world, a girl. Here, as they say, be dragons. But none of this happens before Ariel comes across an artifact from an earlier civilization, a sentient, record-keeping artificial intelligence that carries with it the perspective of the whole of human history—and becomes both Ariel's greatest ally and the narrator of our story. Moonbound is an adventure into the richest depths of Story itself. It is a deeply satisfying epic of ancient scale, blasted through the imaginative prism one of our most forward-thinking writers. And this is only the beginning. A Macmillan Audio production from Farrar, Straus and Giroux.